2016
DOI: 10.5966/sctm.2015-0386
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Cardioprotection by Human Endometrium Mesenchymal Stem Cells Driven by Exosomal MicroRNA-21

Abstract: Our group recently reported positive therapeutic benefit of human endometrium‐derived mesenchymal stem cells (EnMSCs) delivered to infarcted rat myocardium, an effect that correlated with enhanced secretion of protective cytokines and growth factors compared with parallel cultures of human bone marrow MSCs (BMMSCs). To define more precisely the molecular mechanisms of EnMSC therapy, in the present study, we assessed in parallel the paracrine and therapeutic properties of MSCs derived from endometrium, bone mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
213
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 231 publications
(222 citation statements)
references
References 43 publications
4
213
0
5
Order By: Relevance
“…The latest data showed that miR-21 played a vital role in MSC-Exo-mediated effects on cardiac contractility and calcium handling, probably via PI3K signaling (38). In addition, miR-21 mediated the proangiogenic effects of exosomes on endothelial cells (37,39), and consistently we found the exosomes derived from DSAP-MSCs enhanced angiogenesis after MI via miR-21. Thus, the elevated level of miR-21 in DSAP-MSC-Exos partly accounted for the molecular mechanisms underlying It has been reported that the degree of cell attachment of SAP was relatively low due to the lack of adhesion motif.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The latest data showed that miR-21 played a vital role in MSC-Exo-mediated effects on cardiac contractility and calcium handling, probably via PI3K signaling (38). In addition, miR-21 mediated the proangiogenic effects of exosomes on endothelial cells (37,39), and consistently we found the exosomes derived from DSAP-MSCs enhanced angiogenesis after MI via miR-21. Thus, the elevated level of miR-21 in DSAP-MSC-Exos partly accounted for the molecular mechanisms underlying It has been reported that the degree of cell attachment of SAP was relatively low due to the lack of adhesion motif.…”
Section: Discussionsupporting
confidence: 63%
“…We also found that miR-21 contributed to the improvement of cardiac function after DSAP-MSC-Exo injection in rat model of MI. miR-21 is a well-known cardioprotective microRNA, and it has been confirmed that exosomal miR-21 was a major cardioprotective paracrine factor produced by MSCs through the phosphatase and tensin homolog deleted on chromosome 10/Akt pathway (36,37). The latest data showed that miR-21 played a vital role in MSC-Exo-mediated effects on cardiac contractility and calcium handling, probably via PI3K signaling (38).…”
Section: Discussionmentioning
confidence: 91%
“…Left ventricular ejection fraction (LVEF) and fractional shortening (FS) were calculated as previously described [20] and shown in Supplemental Table S1.…”
Section: Methodsmentioning
confidence: 99%
“…In vitro and in vivo studies from our laboratory have demonstrated that exosomes derived from MSCs have an immunomodulatory potential against in vitro activated T cells (Blazquez et al, ) as well as an anti‐inflammatory effect in an antigen‐induced synovitis animal model (Casado et al, ). In two recent papers from Chen, Xiang, Wang, and Xiang () and Wang et al (), it was found that the potent paracrine effect of endMSCs was mediated by secreted exosomes. In the first report, a cardioprotective effect (antiapoptotic and proangiogenic) was demonstrated through the release of miR‐21 (Wang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In two recent papers from Chen, Xiang, Wang, and Xiang () and Wang et al (), it was found that the potent paracrine effect of endMSCs was mediated by secreted exosomes. In the first report, a cardioprotective effect (antiapoptotic and proangiogenic) was demonstrated through the release of miR‐21 (Wang et al, ). In the second report, the exosomes from endMSCs showed an antiapoptotic capacity in the setting of fulminant hepatic failure.…”
Section: Introductionmentioning
confidence: 99%